2005
DOI: 10.1007/s10751-006-9265-x
|View full text |Cite
|
Sign up to set email alerts
|

Mössbauer and XRD study of pulse plated Fe–P and Fe–Ni thin layers

Abstract: 57 Fe conversion electron Mössbauer spectroscopy, X-ray diffraction, electrochemical and magnetic measurements were used to study pulse electroplated Fe-P and NiFe coatings. XRD and 57 Fe CEMS measurements revealed the amorphous character of the novel pulse plated Fe-P alloys. CEM spectra indicated significant differences in the short range order and in the magnetic anisotropy between the Fe-P deposits pulse plated at medium long deposition time (t on =2 ms), with short relaxation time (t off =9 ms) and low cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The phosphorus content of the deposits depends on many deposition parameters, such as bath composition, current density and temperature [27,30,33]. The composition range of amorphous structures can be extended towards lower phosphorus contents using pulsed deposition current [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…The phosphorus content of the deposits depends on many deposition parameters, such as bath composition, current density and temperature [27,30,33]. The composition range of amorphous structures can be extended towards lower phosphorus contents using pulsed deposition current [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Amorphous alloys can exhibit a combination of striking characteristics, like magnetic [1][2][3] and mechanical [4] properties, as well as corrosion resistance [5,6], owing to their single-phase nature related with the lack of structural defects like grain boundaries and dislocations. Alloying transition metals with metalloids such as P, B, C, and Si can render amorphous phases.…”
Section: Introductionmentioning
confidence: 99%
“…Even low concentrations show an influence on the quality of the iron deposits. The structural characterization of the deposited Fe-P films was performed by X-ray diffraction (XRD) measurements [15] and Mossbauer spectroscopy [3,13,21]. These investigations revealed that a P content over 14 at.% resulted in amorphous-like coatings.…”
Section: Introductionmentioning
confidence: 99%